Decoding PARP roles in breast cancer therapy resistance - Mohammad Abohassan; Farag M. Altalbawy; Majid S. Jabir; Thikra F. Hasan; Ashishkumar Kyada; Deepak Nathiya; Parjinder Kaur; M. Ravi Kumar; Munthar Kadhim Abosaoda; Muhammad Shahid Iqbal (Molecular Biology Reports, 2026)

Cross-Sectional Survey of Physician-Reported Usage Patterns and GC–MS Phytochemical Profiling of Mahabala Tailam - Anoop A.K.; P. M. Varier; Ramesh P.R.; Haritha N.; Arjun M.K.; Deepak M.; Venugopalan P (Journal of Pharmaceutical Innovation, 2026)

Decoding Consumer Decisions: The Role of Food Labels in Sustainability and the Circular Economy - Priya K M; Nayana Prabhash; Deepak Ramanan Veera Raghavan (Circular Economy and Sustainability, 2026)

LAMP-assisted CRISPR-Cas12a platform for detection of Bacillus anthracis spores in environmental samples - Borse Rushikesh Sanjay; Maria Anto Dani Nishanth; Jess Vergis; Niveditha Pollumahanti; Laxman Chatlod; Yogesh Gadekar; M. Muthukumar; Baswa P. Reddy; Satya Veer Singh Malik; Sukhadeo Baliram Barbuddhe; Deepak Bhiwa Rawool (Analytica Chimica Acta, 2026)

AMBMP Hydrochloride Reverses STZ-Induced Alzheimer-Type Dementia Associated with Wnt/β-catenin/TLR4 Signaling - Palak Kalra; Deepak Chaturvedi; Amit Kumar; Amarjot Kaur Grewal; Heena Khan; Varinder Singh; Thakur Gurjeet Singh; Tanveer Singh; Sheikh F. Ahmad; Sabry M. Attia (NeuroMolecular Medicine, 2026)

Enhanced lithium-ion battery health prognosis for electric vehicles using complex-value spatio-temporal graph convolutional neural networks and bitterling fish optimization algorithm - K. Dhineshkumar; N. Vengadachalam; K. Yogeshwaran; M. Deepak (Process Safety and Environmental Protection, 2026)

7-Hydroxyflavone mitigates partial sciatic nerve ligation–induced neuropathic pain via modulation of oxidative and inflammatory pathways - Ashish D. Tale; Shirish P. Jain; Siddharth V. Kamble; Sachin P. Borikar; Shailesh M. Kewatkar; Deepak K. Lokwani; Satish P. Shelke; Dipak V. Bhusari; Sangameshwar B. Kanthale (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Racial and ethnic disparities in esophageal cancer survival are greatest at curable stages: a population-based study - Saurabh Kalra; Cindy Medina Pabón; Deepak Kalra; WayWay M. Hlaing; Paulo S. Pinheiro (Cancer Causes & Control, 2026)
Background Racial and ethnic disparities in esophageal cancer outcomes are documented, but whether they differ by stage at diagnosis is unclear. Using population-based data from Florida, a diverse, Medicaid non-expansion state, we conducted a stage-stratified analysis of racial/ethnic differences in survival and treatment receipt. Methods We analyzed 21,814 esophageal cancer cases from the Florida Cancer Data System (2005–2021). Using cause-specific Cox models, we estimated adjusted hazard ratios (aHRs) for cancer-specific mortality overall and by stage, adjusting for demographics, tumor characteristics, treatment, smoking, and socioeconomic factors. Multivariable logistic regression assessed racial/ethnic differences in receipt of surgery, chemotherapy, and radiation. Results Patients were 81.0% non-Hispanic (NH) White, 8.0% NH Black, and 10.0% Hispanic. NH Black patients had higher overall mortality than NH White patients (aHR: 1.08; 95% CI 1.02–1.15). Stage-stratified models showed elevated mortality among NH Black patients at localized (aHR: 1.24; 95% CI 1.05–1.45) and regional stages (aHR: 1.19; 95% CI 1.07–1.35) compared with NH White patients, but lower mortality at distant stage (aHR: 0.88; 95% CI 0.80–0.98). NH Black patients had lower odds of surgery (aOR: 0.51; 95% CI 0.43–0.61) and chemotherapy (aOR: 0.79; 95% CI 0.70–0.90) compared with NH White patients; radiation receipt did not differ. Conclusion Survival disparities were most pronounced at curable stages, indicating inequities in post-diagnosis management. Lower treatment receipt and persistent survival differences after clinical adjustment suggest that structural and systemic factors contribute. These findings highlight a critical target for cancer control and underscore the need for system-level reforms to ensure equitable, stage-appropriate care.

LC–MS-based phytochemical analysis and drug-likeness prediction of KB yoga: an ayurvedic polyherbal formulation - Vivek Palengara; P. B. Benil; M. Deepak; N. Manojkumar (Vegetos, 2026)

Editorial Expression of Concern: Chloride channels and mast cell function: pioneering new frontiers in IBD therapy - Ahmed M. Aljameeli; Bader Alsuwayt; Deepak Bharati; Vaishnavi Gohri; Popat Mohite; Sudarshan Singh; Vijay Chidrawar (Molecular and Cellular Biochemistry, 2026)

Design and Development of Myco-Mediated Bioremediation System for the Treatment of Runoff and Grey Water - Anupam Barh; Uday Mandal; J. M. S. Tomar; Deepak Singh; Varun Chauhan; Sudheer Kumar Annepu; Rama Pal; M. Muruganandam; Trisha Roy; A. C. Rathore; A. K. Gupta; Devideen Yadav; et al. (Water, Air, & Soil Pollution, 2026)

TransEndocardial Injection of Autologous Expanded CD34+ Stem Cells (ProtheraCytes®) after myocardial infarction: Impact on Patients’ Quality of Life - Jérôme Roncalli; François Roubille; Philippe Henon; Pierre-Yves Marie; Gilles Montalescot; Deepak L. Bhatt; Guillaume Trebuchet; Matthieu de Kalbermatten; Ibon Garitaonandia; David M. Smadja (Stem Cell Reviews and Reports, 2026)

Exploring the Generalization Limits of UNet Variants in Road Extraction - T. V. Jayakumar; Deepak Mishra; M. Ramiya Anandakumar; Jai G. Singla (Journal of the Indian Society of Remote Sensing, 2026)

Metabolite profiling and evaluation of anti-oxidant and immunomodulatory activity of Aswagandha Tablet, an Ayurvedic proprietary herbal preparation - Sulaiman C T; Arshad Jouhar T; Deepak M; Anandan E M; Indira Balachandran (Vegetos, 2026)

Intelligent quantification of ecotoxic fungicide in viticultural environment using AI-driven non-isotropic GPR integrated electrochemical sensor - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Qianqiao Chen; Salman S. Alharthi; Hamed M. Al-Saidi (Journal of Environmental Chemical Engineering, 2026)

Stage-specific GWAS identifies a pleiotropic ankyrin repeat locus near GmSALT3 for salinity tolerance in soybean - Preetkumar H. Trivedi; Janhavi Gadhawe; Shreyas M. Salvi; Snehaben M. Dodia; Deepak Pawar; Abhinandan S. Patil (Plant Cell Reports, 2026)

Unraveling cellular longevity pathways in poultry under heat stress: functional and computational characterization of the adaptogenic formulation Phytocee™ - K. Shamana; R. Edwin; S. P. Jaishree; D. Prashanth; G. Aboli; M. Deepak (In Silico Pharmacology, 2026)

Electrochemical quantification of O-phenylphenol in citrus fruits and oilseeds using β-CD-carbon black/CuCo2O4 nanocomposite - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Aiswarya H N; Salman S. Alharthi; Hamed M. Al-Saidi (Food Control, 2026)

Long-term ecological recovery of a minespoil watershed: Hydrological, vegetation, and carbon stock assessment - Jag Mohan Singh Tomar; Anupam Barh; Raj Kumar; Deepak Singh; Ranjeet Singh; Dinesh Jinger; R.K. Singh; Rajesh Kaushal; Sneha Dobhal; M. Madhu (Ecological Engineering, 2026)

From atmosphere to lungs: health risks of airborne microplastics in public spaces - S N Sruthi; C. Krishna Deepak; Sivan Sangeetha; Appukuttan Saritha; M S ShyleshChandran (Air Quality, Atmosphere & Health, 2026)

Synthesis, Photophysical and Aggregation Induced Emission Property of New 4-(4-cyanophenyl)-2-oxo-6-(thiophen-2-yl)-1,2-dihydropyridine-3-carbonitrile - Samrudhi B. M; Shibani Salian; Abdennacer Idrissi; Said Bouzakraoui; Deepak Devadiga; Ahipa T. N. (Journal of Fluorescence, 2026)

Challenging the Alternaria, great havoc of concern to many crop plants with special reference to sunflower- epidemiology and integrated management - Ajith C R; Sudheendra A. Ashtaputre; Laxminarayana Rao M. S.; Vijayakumar A. Giritammannavar; Milind P. Potdar; Ramaraddi N. Madalli; Deepika Gakhar; Deepak Bhanot; Anurag Malik (Journal of Plant Pathology, 2026)

Ai-powered decision-support system for maize Turcicum Leaf Blight: Novel ensemble models for disease forecasting with integrated fungicide advisory - G. Jadesha; Anupkumar M Bongale; H.C. Lohithaswa; N.B. Prakash; M.K.Prasanna Kumar; D. Deepak; Shreyans S Gadekar; Anurag Dhole; Yamanura Madival; R.Mohan Kumar; Deepak Dharrao (Computers and Electronics in Agriculture, 2025)

Tracing genotoxic malachite green contamination in aquatic environment using α-Co₂V₂O₇/PAH-CNTs-based electrochemical sensor - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; H.N. Aiswarya; Salman S. Alharthi; Hamed M. Al-Saidi (Journal of Environmental Chemical Engineering, 2025)

Quantification of systemic fungicide in stone fruits and nuts based on PVP/CNF-COOH embedded CuCo2O4 tertiary nanocomposite - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Salman S. Alharthi; Hamed M. Al-Saidi (Food Chemistry, 2025)

Influence of modified atmospheric storage conditions on seed longevity and health of maize genotypes (Zea mays L.) - T. N. Deepak; S. N. Vasudevan; Palanimuttu; P. Mahadevu; M. Shobharani; R. Siddaraju; Parashivamurthy; Thimmegowda (Cereal Research Communications, 2025)

First report of Lasiodiplodia pseudotheobromae causing stem rot of sapota in India - G. S. Madhu; A. T. Rani; B. M. Muralidhara; G. Nayan Deepak; S. Rajendiran; V. Venkataravanappa (Journal of Plant Pathology, 2025)

Biogenic synthesis of CuO-TiO2 nanocomposites from Senna auriculata (L.) Roxb. Plant extract and its evaluation of antioxidant, antibacterial and anticancer activity of HepG2 cell lines - Manickam Rajkumar; S.I. Davis Presley; M. Yasmin Begum; Ali Alamri; Adel Al Fatease; Koyeli Girigoswami; Prabha Govindaraj; Shobana Sampath; Rajaram Madhankumar; Paramasivam Deepak (Biocatalysis and Agricultural Biotechnology, 2025)

Insights into the roles of metallic and coordinatively unsaturated cobalt sites in efficient 1,5-pentanediol production - Asier Barredo; Nerea Viar; Jesús M. Requies; Deepak Verma; Jaehoon Kim; Inaki Gandarias (Chemical Engineering Journal, 2025)

Seaweed extract-based biostimulants alleviate nutrient stress and enhance productivity and grain quality of wheat through efficient use of fertilizers nutrients under sub-optimal NPK application - Bijan Kumar Mondal; Abir Dey; M. C. Meena; Debarup Das; Archana Singh; Shivani Nagar; Prasenjit Ray; P. K. Upadhyay; Deepak Bamel; Amit Kumar Dash; Krishna Kumar Mourya; Narender Yadava; et al. (Journal of Applied Phycology, 2025)

Rheotaxis and hygropetry governs the behaviour of Pirenella cingulata populations on a tropical mesotidal mudflat - Ranjana Yadav; F. Pathan; Aniket Desai; Deepa Shashikant Yogi; R.P. Deepak; Kuniyil Nandakumar; M. Nanajkar; S. Shetye; S. Damare (Marine Environmental Research, 2025)

New insight into the shallow sub-surface for geothermal prospection of Puga valley, Ladakh, India from electrical resistivity tomography - Dewashish Kumar; Arun Kumar Ojha; Ved Prakash Maurya; M. Satyanarayanan; Ratnakar Dhakate; Prakash Kumar; Deepak Kumar; Jitendra Singh Rathore (Geothermics, 2025)

Toward accurate estimation of respiratory rate from the photoplethysmogram: effect of different window period of PPG signals - M. S. Ganeshmurthy; R. Periyasamy; Deepak Joshi (Physical and Engineering Sciences in Medicine, 2025)

Multigene phylogeny and diversity of Phytophthora and Phytopythium species associated with avocado root rot in India and development of a point-of-care LAMP assay for Phytophthora cinnamomi and Phytopythium vexans - G.S. Madhu; A.T. Rani; B.M. Muralidhara; G. Nayan Deepak; S. Rajendiran; M. Ayyandurai; V. Venkataravanappa (Physiological and Molecular Plant Pathology, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Seismic retrofitting of an existing non-ductile open-ground story RC frame by partial infilling with RC shear walls: An experimental study - Abhilash Mallikarjuna; Deepak Yadav; Rahul Bhartiya; Romanbabu M. Oinam; Dipti Ranjan Sahoo (Engineering Structures, 2025)

Biofunctional plant fibers and their bioactive-based materials: A critical review - Mohammed Alsafran; Deepak M. Kasote (Biocatalysis and Agricultural Biotechnology, 2025)

Chloride channels and mast cell function: pioneering new frontiers in IBD therapy - Ahmed M. Aljameeli; Bader Alsuwayt; Deepak Bharati; Vaishnavi Gohri; Popat Mohite; Sudarshan Singh; Vijay Chidrawar (Molecular and Cellular Biochemistry, 2025)

Conservation of native tree species in the agroforest of rice-based agroecosystems will contribute to sustainable agriculture - Merlin Lopus; Amit Kushwaha; M. D. Reshma; Subaiba Shafi; Abdulla Habeeb; Telna Sebastian; Deepak Jaiswal; V. Shakeela (Biodiversity and Conservation, 2025)

Interference of PFAS sorption on zeolites from natural water characteristics - Nathaniel P. Sheehan; Charles A. Ponge; Abe Pankratz; Justin M. Hutchison; Brian B. Laird; Nuong P. Nguyen; Mark B. Shiflett; Deepak Timalsina; Michael Zhuo Wang; Edward F. Peltier (Chemosphere, 2025)

Mangrove Community Structure Following Dieback Events in the Maldives: Special Emphasis on the Genus Bruguiera - S. Sreelekshmi; Deepak Jose; B. Aneesh; Aishath Farhath Ali; S. Bijoy Nandan; K. Avarachen Mathew; M. Harikrishnan; P. Hari Praved (Thalassas: An International Journal of Marine Sciences, 2025)

Unraveling the mechanism of biotransformation in Mesosphaerum suaveolens (L.) Kuntze. and Ocimum basilicum L. solid and suspension cultures using 4-hydroxybenzoic acid and hydroquinone as precursors - M. Riddhi; A. Deepak; P. Parth; K. Monisha (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Hybrid AI models for thermal imaging and analysis of neurological disorders using thermoplasmonics - Y. Ravi Kumar; M. Vanitha; KDV Prasad; Kanchan Bala; Deepak Gupta; P. Venkateswara rao (Journal of Thermal Biology, 2025)

Identifying capacity limitations and training needs using a stock assessment game - André E. Punt; Catherine M. Dichmont; Natalie A. Dowling; Roy A. Deng; Sean Pascoe; Ingrid van Putten; Pia Bessell-Browne; Paul Burch; Owen Burnell; Rowan C. Chick; Simon de Lestang; Ainslie Denham; et al. (Fisheries Research, 2025)

Genome-wide exploration of soybean domestication traits: integrating association mapping and SNP × SNP interaction analyses - Abhinandan S. Patil; Manoj D. Oak; Shreyash Gijare; Aditya Gobade; Santosh Jaybhay; Vilas D. Surve; Suresha P. G.; Dattatraya Salunkhe; Balasaheb N. Waghmare; Bhanudas Idhol; Ravindra M. Patil; Deepak Pawar (Plant Molecular Biology, 2025)

Characterization of multichannel SDD X-ray spectrometer with ASIC readout - Nishant Singh; M. Shanmugam; Arpit Patel; Sushil Kumar; Deepak K. Painkra; Tinkal Ladiya; S. Vadawale (Advances in Space Research, 2025)

Ultrasensitive quantification of neonicotinoid thiamethoxam in environment using MOF-derived CuCo2O4/3D rGO based electrochemical sensor integrated with optimized neural network - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Salman S. Alharthi; Hamed M. Al-Saidi (Environmental Research, 2025)

Assessment of polymetallic nodules in the Central Indian Ocean Basin: factors influencing distribution patterns through high‑resolution autonomous underwater vehicle (AUV) survey - V. B. Subin Raj; M. A. Sarun Lal; R. S. Gowri; S. Ramesh; N. R. Ramesh; R. Ramesh; V. Deepak; A. Vadivelan; G. A. Ramadass (Geo-Marine Letters, 2025)

Cuprospinel decorated biopolymer functionalized CNFs based electrocatalytic platform integrated with grid search optimized neural network for detection of vital amino acid in beverages - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Salman S. Alharthi; Hamed M. Al-Saidi (Food Chemistry, 2025)

Pleural Fluid Calprotectin Levels in Benign and Malignant Pleural Effusions and Its Significance in Predicting Success of Pleurodesis in Malignant Pleural Effusions - Amartya Chakraborti; Nishant Kumar Chauhan; Naveen Dutt; Mithu Banerjee; Ravisekhar Gadepalli; Deepak Vedant; M. K. Garg; Gopal Durgeshwar; Hariharan Iyer (Indian Journal of Clinical Biochemistry, 2025)

A multi-gene phylogeny of the Asian kukri snakes (Oligodon Fitzinger, 1826): Sharpening the blade of the second largest serpent radiation (Reptilia: Squamata: Colubridae) - Justin L. Lee; Platon V. Yushchenko; Chatmongkon Suwannapoom; Parinya Pawangkhanant; L. Lee Grismer; Tan Van Nguyen; V. Deepak; Surya Narayanan; Sandeep Das; Thy Neang; H.T. Lalremsanga; Jian-Huan Yang; et al. (Molecular Phylogenetics and Evolution, 2024)

A critical review on Pulicaria species occurring in Qatar: traditional uses, phytochemistry and biological activities - Deepak M. Kasote; Malik Adil Nawaz; Kamal Usman; Najeeb Ullah; Mohammed Alsafran (Phytochemistry Reviews, 2024)
In Qatar, three main species of Pulicaria (from Asteraceae) such as Pulicaria undulata (L.) C.A.Mey, Pulicaria gnaphalodes (Vent.) Boiss. and Pulicaria sicula (L.) Moris are reported. Traditionally, these species have almost the same ethnomedical uses, including their use as herbal tea. This could be because of morphological similarities among some of these species, which also results in taxonomic ambiguity. Altogether, this indicates that these species need to be reviewed comparatively, to understand the phytochemical uniqueness and therapeutic significance of each species individually, including species differentiation at the subspecies level. Hence, this review aims to comparatively review the available literature about traditional uses, phytochemistry, and bio-activities of these species. Being aromatic plants, the chemical composition of essential oils of these species has been extensively studied and reported over 300 volatile organic compounds. Among these, oxygenated monoterpenes and sesquiterpenes are dominant. The diverse and distinguishable composition of essential oils can differentiate P. undulata and Pulicaria crispa (Forssk.) Oliv. (Synonyme: Pulicaria undulata subsp. undulata ). Likewise, flavonoids and sesquiterpenes are the most reported classes of compounds in non-essential oil fractions. Various biological and pharmacological activities are reported to the essential oils, crude extracts, and their fractions, or isolated compounds of these species. Among these, antimicrobial, anticancer, and anti-oxidant activities were mostly investigated, mainly under in vitro conditions. Several distinguishable compounds are listed for each species that can potentially be used as chemical markers while characterizing these species. Most of the traditional claims of these species are validated in recent scientific studies. However, further detailed in vivo clinical interventions are needed for their potential use as therapeutic agents.

Genome-wide association study identified QTLs and genes underlying early seedling vigour in aus rice (Oryza sativa L.) - Firos T. M. Basha; Puranjoy Sar; Prolay K. Bhowmick; Anima Mahato; Deepak S. Bisht; Mir A. Iquebal; Koushik Chakraborty; Amrita Banerjee; Bibhash C. Verma; Debarati Bhaduri; Jitendra Kumar; Umakanta Ngangkham; et al. (Molecular Genetics and Genomics, 2024)

Convective structures of salt fingers at a neutrally buoyant density interface - Deepak Kumar Singh; O. P. Singh; K. M. Nihaal; U. S. Mahabaleshwar (Environmental Fluid Mechanics, 2024)

Toxicological impacts of plastic microfibers from face masks on Artemia salina: An environmental assessment using Box-Behnken design - Devlina Das Pramanik; Armeena Sharma; Deepak Kumar Das; Arindam Pramanik; Paul Kay; Francisco M. Goycoolea (Marine Environmental Research, 2024)

Polarimetric characterization of Chandrayaan-3 landing site near lunar south pole using high resolution Chandrayaan-2 DFSAR data - Tathagata Chakraborty; Dharmendra Kr. Pandey; Raghav Mehra; Parikshit Parasher; Deepak Putrevu; V.M. Ramanujam; Nilesh M. Desai (Planetary and Space Science, 2024)

Standardized total tract digestibility of phosphorus in canola meal fed to gestating or lactating sows without or with a multi-enzyme complex - Deepak E. Velayudhan; Manik M. Hossain; Jinyoung Lee; Hans H. Stein; Charles Martin Nyachoti (Animal Feed Science and Technology, 2024)

Influence of biochar amendment on removal of heavy metal from soils using phytoremediation by Catharanthus roseus L. and Chrysopogon zizanioides L. - Dhritilekha Deka; Deepak Patwa; Archana M. Nair; Karangat Ravi (Environmental Science and Pollution Research, 2024)

Magnetic anomalies of randomly magnetized finite-strike listric fault sources - M Deepak; B Ramamma; V Chakravarthi (Journal of Earth System Science, 2024)

Accelerating vascular graft development: Adipose-derived stem cells and PODS® (Polyhedrin delivery system with tissue-specific growth factors) – Enhanced 3D bioprinting for functional blood vessels - Sushma Priya; Ashleigh S. Boyd; Abril Torres-Bautista; Prasad Sawadkar; Ash Mosahebi; Subha Narayan Rath; Deepak M. Kalaskar (Chemical Engineering Journal, 2024)

Proteomic analysis of lung responses to SARS-CoV-2 infection in aged non-human primates: clinical and research relevance - Andreu Garcia-Vilanova; Anna Allué-Guardia; Nadine M. Chacon; Anwari Akhter; Dhiraj Kumar Singh; Deepak Kaushal; Blanca I. Restrepo; Larry S. Schlesinger; Joanne Turner; Susan T. Weintraub; Jordi B. Torrelles (GeroScience, 2024)

Ruthenium doping of NASICON electrolyte augments the performance of solid-state sodium-ion batteries - M. Dinachandra Singh; Deepak Kumar Gorai; Kumar Brajesh; Pragati Singh; Vishal Ranawade; Ajay Vijay Shinde; M. Jareer; Raju Gupta; Ashish Garg; Vishal Agarwal; Kanwar S. Nalwa (Chemical Engineering Journal, 2024)

Polyethylene terephthalate waste derived nanomaterials (WDNMs) and its utilization in electrochemical devices - J. Manjunathan; K. Pavithra; Senthilkumar Nangan; S. Prakash; Kuldeep K. Saxena; Kuldeep Sharma; Khursheed Muzammil; Deepak Verma; Jenita Rani Gnanapragasam; R. Ramasubburayan; M. Revathi (Chemosphere, 2024)

Development and techno-economic analysis of Grewia biopolymer-based dual coagulant system for wastewater treatment at pilot scale - Kameni Ngounou M. Bernard; Om Prakash; Charu Juneja; Deepak Panchal; Ndi K. Sylvere; Sukdeb Pal (Bioresource Technology, 2024)

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Multipath phase based vegetation correction scheme for improved field-scale soil moisture retrieval over agricultural cropland using GNSS-IR technique - Sushant Shekhar; Rishi Prakash; Dharmendra Kumar Pandey; Anurag Vidyarthi; Prashant K. Srivastava; Deepak Putrevu; Nilesh M. Desai (Advances in Space Research, 2024)

Preservation of plant‐wax biomarkers in deserts: implications for Quaternary environment and human evolutionary studies - Deepak Kumar Jha; Robert Patalano; Jana Ilgner; Hema Achyuthan; Abdullah M. Alsharekh; Simon Armitage; James Blinkhorn; Nicole Boivin; Paul S. Breeze; Ravindra Devra; Nicholas Drake; Huw S. Groucutt; et al. (Journal of Quaternary Science, 2024)
Analysis of plant‐wax biomarkers from sedimentary sequences can enable past environmental and hydrological reconstruction and provide insights into past hominin adaptations. However, biomarker preservation in desert contexts has been considered unlikely given the sparse nature of the vegetation within the landscape. Here we evaluate the preservation of n ‐alkanes and fatty acids collected from four depositional sequences associated with archaeological contexts in the Nefud Desert, Saudi Arabia, and the Thar Desert, India. Pleistocene and Holocene samples were selected to understand the effects of age on preservation. The results of molecular distribution patterns and indices, particularly the high carbon preference index and average chain length, show the preservation of plant‐wax biomarkers in both the Holocene and Pleistocene desert sequences, while δ 13 C values and organic content provide insights into the vegetation contributing to the plant‐wax organic pool. This study provides a baseline for understanding human–environment interactions and for reconstructing changes in arid land habitats of relevance to hominins during the Quaternary.

Nanomolar electrochemical detection of feed additive ractopamine in meat samples using spinel zinc ferrite decorated 3-dimensional graphene nanosheets to combat food fraud in livestock industries - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Salman S. Alharthi; Hamed M. Al-Saidi; Deepak Kumar (Food Chemistry, 2024)

Clinical, epidemiological, and molecular investigation of Kyasanur forest disease from Karnataka state, India during 2018-2019 - Ashok Munivenkatappa; Pragya D. Yadav; Rima R. Sahay; Kiran SK; Anita M. Shete; Deepak Y. Patil; Sreelekshmy Mohandas; Rajlaxmi Jain; Savita Patil; Diamond P. Sinha; Manjunatha M. Jayaswamy (Infectious Diseases, 2024)

Occurrence of Multidrug-Resistant (MDR) Extended-Spectrum Beta-lactamase (ESBL)-Producing Escherichia coli in Wastewater and Natural Water Sources from the Eastern Part of Uttar Pradesh, India - Kaushik Satyaprakash; Pavan Kumar Pesingi; Annada Das; M. R. Vineeth; Satya Veer Singh Malik; Sukhadeo B. Barbuddhe; Deepak Bhiwa Rawool (Water, Air, & Soil Pollution, 2024)

Synthetic Strategies for 3,6-Substituted Carbazole-based Polymers and Their Opto-Electronic Applications—A Review - Srikanth G.; Deepak Devadiga; Samrudhi B. M.; Ahipa T. N. (Journal of Fluorescence, 2024)

Ultrasensitive detection and photocatalytic degradation of polyketide drug tetracycline in environment and food samples using dual-functional Ag doped zinc ferrite embedded functionalized carbon nanofibers - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Guo-Ting Hong; Salman S. Alharthi; Hamed M. Al-Saidi (Chemosphere, 2024)

Data-driven irrigation scheduling increases the crop water use efficiency of Cabernet Sauvignon grapevines - Rochelle Schlank; Catherine M. Kidman; Deepak Gautam; David W. Jeffery; Vinay Pagay (Irrigation Science, 2024)
In the context of water management in agriculture, irrigation scheduling is critically important as it optimises water application to crops and can also target specific production goals. However, there is no consensus on the ideal irrigation scheduling strategy regarding crop water use efficiency ( WUE c ). In a premium Cabernet Sauvignon vineyard in Coonawarra, South Australia, over three growing seasons, irrigation scheduling strategies based on experience or historical knowledge (‘GROW’ treatment) were compared to data-driven strategies including crop evapotranspiration, and plant and soil water status thresholds to evaluate their effects on leaf- and vine-level WUEs. A final treatment, GROW + , that doubled the GROW level of irrigation was also evaluated in the third season. The WUE metrics were determined at the leaf, vine, and fruit scales as intrinsic WUE ( WUE i ), crop WUE ( WUE c ), and carbon isotope ratio (δ 13 C), respectively. Furthermore, the irrigation strategies were evaluated in the background of two contrasting soil types: Terra Rossa (light clay, well-drained) and Rendzina (heavier clay, poorly drained). Seasonal soil and vine water status, leaf gas exchange, and light interception were measured, and yield components and pruning weights were obtained following harvest. The amount of seasonal irrigation water based on the data-driven strategies was up to 65% lower across both soil types compared with the GROW or GROW + approaches. WUE i and δ 13 C were largely similar between treatments. However, for vines grown on Terra Rossa soil, little to no yield penalty was observed when data-driven irrigation scheduling was applied, in addition to increased WUE c values of up to 41%. It can be concluded that irrigation scheduling decisions based on data were superior to the conventional irrigation scheduling method on account of reducing irrigation water volume and increasing WUE, particularly in Terra Rossa soils.

Israel−Palestine Conflict: Risk of Sleep Disorders and Post-Traumatic Stress Disorders - Seithikurippu R. Pandi‑Perumal; Kamalesh K. Gulia; Hruda Nanda Mallick; Deepak Shrivastava; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Konda Mani Saravanan; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Derebe Madoro; Meera Narasimhan; et al. (Sleep and Vigilance, 2023)

Tea (Camellia sinensis (L.) Kuntze) as an emerging source of protein and bioactive peptides: A narrative review - Manoj Kumar; Pavidharshini Selvasekaran; Ramalingam Chidambaram; Baohong Zhang; Muzaffar Hasan; Om Prakash Gupta; Nadeem Rais; Kanika Sharma; Anshu Sharma; José M. Lorenzo; E. Parameswari; Vishal P. Deshmukh; et al. (Food Chemistry, 2023)

Review on recent trends in the application of protein concentrates and isolates – A food industry perspective - M. Meganaharshini; V. Sudhakar; N. Dhivya Bharathi; S. Deepak (Food and Humanity, 2023)

Geoheritage and Geotourism Sites from the Narmada-Son Fault (NSF) Zone, Narmada River, and Mahi River in Central Mainland Gujarat, Western India - Deepak M. Maurya; Swarali Vasaikar; Laxman S. Chamyal (Geoheritage, 2023)

A Rural Delivery-Based Produce Prescription Intervention Improves Glycemic Control and Stress - Brandon Stroud; Molly M. Jacobs; Deepak Palakshappa; Lauren R. Sastre (Journal of Nutrition Education and Behavior, 2023)

Thunderstorm Nowcasting Using Ground-Based Microwave Radiometer Brightness Temperature Measurements - R. Pushpa Saroja; M. Rajasekhar; C. V. Naidu; S. Rambabu; G. Paparao; C. Deepak (Journal of the Indian Society of Remote Sensing, 2023)

Ziziphus mauritiana-derived nitrogen-doped biogenic carbon dots: Eco-friendly catalysts for dye degradation and antibacterial applications - Subramani Rajapandi; Senthilkumar Nangan; Thirumalaivasan Natesan; Anuj Kumar; Govindaraj Dharman; M. Pandeeswaran; Deepak Verma; Mohd Ubaidullah; Bidhan Pandit; Navdeep Dhaliwal; Satbir S. Sehgal; Rajavel Rangappan; et al. (Chemosphere, 2023)

Marine brown algae (Sargassum wightii) derived 9-hydroxyhexadecanoic acid: A promising inhibitor of α-amylase and α-glucosidase with mechanistic insights from molecular docking and its non-target toxicity analysis - Deepak Paramasivam; Arun Meyyazhagan; Nathiya Thiyagarajulu; Karthiga Arumugasamy; Balamuralikrishnan Balasubramanian; Amer M. Alanazi; Kannan R.R. Rengasamy (South African Journal of Botany, 2023)

Microplastic contamination in Indian rural and urban lacustrine ecosystems - R.L. Laju; M. Jayanthi; K. Immaculate Jeyasanta; Jamila Patterson; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Science of The Total Environment, 2023)

Phosphorus adsorption and organic release from dried and thermally treated water treatment sludge - Minh Duc Nguyen; David Donaldson; Sirjana Adhikari; Negin Amini; Deepak Surendhra Mallya; Michael Thomas; Ellen M. Moon; Nicholas A. Milne (Environmental Research, 2023)

Differential impacts of post-harvest hydrothermal treatments on chemical composition and in vitro digestibility of two brown macroalgae (Fucales, Phaeophyceae), Ascophyllum nodosum and Fucus vesiculosus, for animal feed applications - Deepak Pandey; Geir Næss; António J. M. Fonseca; Margarida R. G. Maia; Ana R. J. Cabrita; Prabhat Khanal (Journal of Applied Phycology, 2023)
This study tested the hypothesis that post-harvest hot water blanching improves the chemical composition, mainly mineral and carbohydrate contents, and in vitro digestibility of two predominant brown macroalgae, Ascophyllum nodosum (AN) and Fucus vesiculosus (FV), as feed ingredients for monogastric and ruminant animals. Low-temperature water blanching (LTB; 40 °C for 5 min) had minor impacts on macroalgal chemical composition and in vitro digestibility. Conversely, high-temperature water blanching (HTB; 80 °C for 5 min) effectively reduced total ash and specific elements, including sodium, potassium, iodine, and arsenic, by ~ 25–73% compared to unblanched algal biomass (more prominently in FV). The HTB raised total sugar contents by ~ 25% in FV, markedly elevating uronic acids (~ 60%) and glucans (~ 33%). However, HTB reduced mannitol (> 50%) and enhanced total polyphenol extractability in both macroalgae. The HTB diminished ~ 8% of in vitro dry matter or organic matter digestibility and 26% of crude protein (CP) digestibility of both macroalgae for monogastric animals and of FV for ruminants (particularly of CP by ~ 42%). Those reduced digestibilities were associated with enriched fibre, uronic acids, total polyphenols, and declined mannitol in the HT-blanched macroalgal biomass. Our findings suggest that hot-water blanching can be an efficient technique to optimise the elemental composition of two fucoid algae, but the altered sugar and complex carbohydrate compositions may impair their digestibility. Future studies should identify appropriate post-harvest processing techniques for brown macroalgae that can optimise both nutritional composition and digestibility along with favourable impacts on feed utilisation and animal performance.

Investigating the mechanical strength, durability and micro-structural properties of slag-based concrete - M. Deepak; Y. Ramalinga Reddy; R. Nagendra (Innovative Infrastructure Solutions, 2023)

Assessment of in-house algorithms on re-entry time prediction of uncontrolled space objects - Pooja Dutt; M. Mutyalarao; P. Bhanumathy; T.R. Saritha Kumari; Deepak Negi; A.K. Anilkumar; Abhay Kumar; V. Ashok (Advances in Space Research, 2023)

Advances and prospects of platelet-rich plasma therapy in veterinary ophthalmology - Khan Sharun; Deepak Chandran; K. M. Manjusha; Pratheesh D. Mankuzhy; Rohit Kumar; Abhijit M. Pawde; Kuldeep Dhama; Hussein M. El-Husseiny; Amarpal (Veterinary Research Communications, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Identifying optimum residue levels for stable crop and water productivity and carbon sequestration under a conservation agriculture based rice-wheat system - Ram Swaroop Bana; Shanti Devi Bamboriya; Vipin Kumar; Samarth Godara; Donald S. Gaydon; Alison M. Laing; Rajkumar Dhakar; Y.S. Shivay; Vijay Singh Meena; Deepak Singh (Soil and Tillage Research, 2023)

Peach (Prunus persica (L.) Batsch) seeds and kernels as potential plant-based functional food ingredients: A review of bioactive compounds and health-promoting activities - Neeraj Kumari; Radha; Manoj Kumar; Sunil Puri; Baohong Zhang; Nadeem Rais; Ashok Pundir; Deepak Chandran; Priya Raman; Sangram Dhumal; Abhijit Dey; Marisennayya Senapathy; et al. (Food Bioscience, 2023)

Removal of gaseous formaldehyde by portable photocatalytic air purifier equipped with bimetallic Pt@Cu-TiO2 filter - Aadil Bathla; Deepak Kukkar; Philippe M. Heynderickx; Sherif A. Younis; Ki-Hyun Kim (Chemical Engineering Journal, 2023)

U-Pb Neoproterozoic age and petrogenesis of a calc-alkaline shoshonitic lamprophyre from Simdega area, Chhotanagpur Gneissic Complex (Eastern India): Implication for the evolution of the Central Indian Tectonic Zone and Rodinia tectonics - Deepak Kumar; N.V. Chalapathi Rao; Aparajita Tripathi; B. Belyatsky; Priyesh Prabhat; Waliur Rahaman; M. Satyanarayanan (Chemical Geology, 2023)

Seasonal and spatial variations in the distribution pattern, sources and impacts of microplastics along different coastal zones of Tamil Nadu, India - K. Immaculate Jeyasanta; M. Jayanthi; R.L. Laju; Jamila Patterson; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Marine Pollution Bulletin, 2023)

Preliminary study of the interactive effects of THC and ethanol on self-reported ability and simulated driving, subjective effects, and cardiovascular responses - Ashley M. Schnakenberg Martin; L. Taylor Flynn; Esra Sefik; Christina Luddy; Jose Cortes-Briones; Patrick D. Skosnik; Brian Pittman; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2023)

Environmental impact of one-step hydrothermal green synthesized ZnO nanoparticles in DI diesel engine performance analysis using duel fuel - S. Ganesan; S. lakshmisankar; Seepana Deepak; M. Selvakumar; S. P. Venkatesan; J. Hemanandh (Nanotechnology for Environmental Engineering, 2023)

Modelling crop yield and harvest index: the role of carbon assimilation and allocation parameters - Hector Camargo-Alvarez; Robert J. R. Elliott; Stefan Olin; Xuhui Wang; Chenzhi Wang; Deepak K. Ray; Thomas A. M. Pugh (Modeling Earth Systems and Environment, 2023)
Crop yield improvement during the last decades has relied on increasing the ratio of the economic organ to the total aboveground biomass, known as the harvest index (HI). In most crop models, HI is set as a parameter; this empirical approach does not consider that HI not only depends on plant genotype, but is also affected by the environment. An alternative is to simulate allocation mechanistically, as in the LPJ-GUESS crop model, which simulates HI based on daily growing conditions and the crop development stage. Simulated HI is critical for agricultural research due to its economic importance, but it also can validate the robust representation of production processes. However, there is a challenge to constrain parameter values globally for the allocation processes. Therefore, this paper aims to evaluate the sensitivity of yield and HI of wheat and maize simulated with LPJ-GUESS to eight production allocation-related parameters and identify the most suitable parameter values for global simulations. The nitrogen demand reduction after anthesis, the minimum leaf carbon to nitrogen ratio (C:N) and the range of leaf C:N strongly affected carbon assimilation and yield, while the retranslocation of labile stem carbon to grains and the retranslocation rate of nitrogen and carbon from vegetative organs to grains after anthesis mainly influenced HI. A global database of observed HI for both crops was compiled for reference to constrain simulations before calibrating parameters for yield against reference data. Two high- and low-yielding maize cultivars emerged from the calibration, whilst spring and winter cultivars were found appropriate for wheat. The calibrated version of LPJ-GUESS improved the simulation of yield and HI at the global scale for both crops, providing a basis for future studies exploring crop production under different climate and management scenarios.

Influence of Nanocarrier Type on the Drug Delivery Aspects of Docetaxel: Empirical Evidences - Saad M. Alshahrani; Nagarani Thotakura; Saurabh Sharma; Sheikh Shahnawaz Quadir; Nishtha Chaurawal; Sumit Sharma; Deepak Chitkara; Kaisar Raza (Journal of Pharmaceutical Innovation, 2023)

4D electrical resistivity to monitor unstable slopes in mountainous tropical regions: an example from Munnar, India - Arnaud Watlet; Hemalatha Thirugnanam; Balmukund Singh; Nitin Kumar M.; Deepak Brahmanandan; Cornelia Inauen; Russell Swift; Phil Meldrum; Sebastian Uhlemann; Paul Wilkinson; Jonathan Chambers; Maneesha Vinodini Ramesh (Landslides, 2023)
The number of large landslides in India has risen in the recent years, due to an increased occurrence of extreme monsoon rainfall events. There is an urgent need to improve our understanding of moisture-induced landslide dynamics, which vary both spatially and temporally. Geophysical methods provide integrated tools to monitor subsurface hydrological processes in unstable slopes at high spatial resolution. They are complementary to more conventional approaches using networks of point sensors, which can provide high temporal resolution information but are severely limited in terms of spatial resolution. Here, we present and discuss data from an electrical resistivity tomography monitoring system—called PRIME—deployed at the Amrita Landslide Early Warning System (Amrita-LEWS) site located in Munnar in the Western Ghats (Kerala, India). The system monitors changes in electrical resistivity in the subsurface of a landslide-prone slope that directly threatens a local community. The monitoring system provides a 4D resistivity model informing on the moisture dynamics in the subsurface of the slope. Results from a 10-month period spanning from pre-monsoon to the end of the monsoon season 2019 are presented and discussed with regard to the spatial variation of soil moisture. The temporal changes in resistivity within the slope are further investigated through the use of time-series clustering and compared to weather and subsurface pore water pressure data. This study sheds new light on the hydrological processes occurring in the shallow subsurface during the monsoon and potentially leading to slope failure. This geophysical approach aims at better understanding and forecasting slope failure to reduce the risk for the local community, thereby providing a powerful tool to be included in local landslide early warning systems.

Social media data extraction for disaster management aid using deep learning techniques - Trisha Vishwanath; Rudresh Deepak Shirwaikar; Washitwa Mani Jaiswal; M. Yashaswini (Remote Sensing Applications: Society and Environment, 2023)

Microbial meat: A sustainable vegan protein source produced from agri-waste to feed the world - Samara Cardoso Alves; Erick Díaz-Ruiz; Bruna Lisboa; Minaxi Sharma; Solange I. Mussatto; Vijay Kumar Thakur; Deepak M. Kalaskar; Vijai Kumar Gupta; Anuj K. Chandel (Food Research International, 2023)

Foliar zinc fertilization improves yield, biofortification and nutrient-use efficiency of upland rice - Akshay Kumar Yogi; Ram Swaroop Bana; Shanti D. Bamboriya; Ram L. Choudhary; Alison M. Laing; Deepak Singh; Samarth Godara; Subhash Babu; Amresh Chaudhary (Nutrient Cycling in Agroecosystems, 2023)

Mitigation of nitrous oxide emissions in grazing systems through nitrification inhibitors: a meta-analysis - Johnny R. Soares; Bruna R. Souza; André M. Mazzetto; Marcelo V. Galdos; Dave R. Chadwick; Eleanor E. Campbell; Deepak Jaiswal; Julianne C. Oliveira; Leonardo A. Monteiro; Murilo S. Vianna; Rubens A. C. Lamparelli; Gleyce K. D. A. Figueiredo; et al. (Nutrient Cycling in Agroecosystems, 2023)
Grasslands are the largest contributor of nitrous oxide (N 2 O) emissions in the agriculture sector due to livestock excreta and nitrogen fertilizers applied to the soil. Nitrification inhibitors (NIs) added to N input have reduced N 2 O emissions, but can show a range of efficiencies depending on climate, soil, and management conditions. A meta-analysis study was conducted to investigate the factors that influence the efficiency of NIs added to fertilizer and excreta in reducing N 2 O emissions, focused on grazing systems. Data from peer-reviewed studies comprising 2164 N 2 O emission factors (EFs) of N inputs with and without NIs addition were compared. The N 2 O EFs varied according to N source (0.0001–8.25%). Overall, NIs reduced the N 2 O EF from N addition by 56.6% (51.1–61.5%), with no difference between NI types (Dicyandiamide—DCD; 3,4-Dimethylpyrazole phosphate—DMPP; and Nitrapyrin) or N source (urine, dung, slurry, and fertilizer). The NIs were more efficient in situations of high N 2 O emissions compared with low; the reduction was 66.0% when EF > 1.5% of N applied compared with 51.9% when EF ≤ 0.5%. DCD was more efficient when applied at rates > 10 kg ha −1 . NIs were less efficient in urine with lower N content (≤ 7 g kg −1 ). NI efficiency was negatively correlated with soil bulk density, and positively correlated with soil moisture and temperature. Better understanding and management of NIs can optimize N 2 O mitigation in grazing systems, e.g., by mapping N 2 O risk and applying NI at variable rate, contributing to improved livestock sustainability.

Application of ultrasonication as pre-treatment for freeze drying: An innovative approach for the retention of nutraceutical quality in foods - Roji Waghmare; Manoj Kumar; Rahul Yadav; Priyank Mhatre; Sachin Sonawane; Swati Sharma; Yogesh Gat; Deepak Chandran; Radha; Muzaffar Hasan; Abhijit Dey; Tanmay Sarkar; et al. (Food Chemistry, 2023)

Mechanically-robust electrospun nanocomposite fiber membranes for oil and water separation - Marat Nueraji; Zhexenbek Toktarbay; Aida Ardakkyzy; Deepak Sridhar; Hassan Algadi; Ben Bin Xu; Jalal T. Althakafy; Abdullah K. Alanazi; Hala M. Abo-Dief; Salimgerey Adilov; Zhanhu Guo (Environmental Research, 2023)

Arsenite and arsenate ions adsorption onto a biogenic nano-iron entrapped dual network Fe@alginate-κ-carrageenan hydrogel beads - Anushree Srivastava; Shivesh Kumar Azad; Kavita Singh; Bablu Prasad; Madhu Kumari; Nandan; Amresh Kumar Sahoo; Hemen Dave; Deepak M. Maurya; Deepak Singh; Kumar Suranjit Prasad (Nanotechnology for Environmental Engineering, 2023)

Microplastic pollution and its implicated risks in the estuarine environment of Tamil Nadu, India - K. Immaculate Jeyasanta; R.L. Laju; Jamila Patterson; M. Jayanthi; Deepak S. Bilgi; Narmatha Sathish; J.K. Patterson Edward (Science of The Total Environment, 2023)

Diffusion mechanism and electrochemical investigation of 1T phase Al–MoS2@rGO nano-composite as a high-performance anode for sodium-ion batteries - Manish Kr. Singh; Jayashree Pati; Deepak Seth; Jagdees Prasad; Manish Agarwal; M. Ali Haider; Jeng-Kuei Chang; Rajendra S. Dhaka (Chemical Engineering Journal, 2023)

Integrated management of Fusarium wilt disease of banana in Kerala, India - N. P. Lishma; K. Anita Cherian; Vimi Louis; R. Sureshkumar; P. Naveen Kumar; Deepak Chandran; M. Pran; Rohit Sharma (Vegetos, 2023)

Cases of SARS-CoV-2 reinfection with Omicron BA.2 post breakthrough infection with Delta and Kappa variants - Rima R. Sahay; Deepak Y. Patil; Gajanan N. Sapkal; Anita M. Shete; Pragya D. Yadav (Infectious Diseases, 2023)

Corrigendum to “Harmonization of acronyms for volatile organic compound metabolites using a standardized naming system” [Int. J. Hygiene Environ. Health 235 (2021) 113749] - Denise S. Tevis; Sharon R. Flores; Brandon M. Kenwood; Deepak Bhandari; Peyton Jacob; Jia Liu; Pawel K. Lorkiewicz; Daniel J. Conklin; Stephen S. Hecht; Maciej L. Goniewicz; Benjamin C. Blount; Víctor R. De Jesús (International Journal of Hygiene and Environmental Health, 2023)

Comprehensive spatio-temporal benchmarking of surface water quality of Hindon River, a tributary of river Yamuna, India: Adopting multivariate statistical approach - Anand Kumar Gupta; Ambrish Kumar; Uma Kant Maurya; Deepak Singh; Sadikul Islam; Avinash Chandra Rathore; Parmanand Kumar; Ravish Singh; M. Madhu (Environmental Science and Pollution Research, 2022)

Anti-oxidant, anti-proliferative activities and characterization of secondary metabolites using Q-TOF-LC-MS/MS analysis of anti-aging medicinal plant Holostemma ada-kodien - M Deepak; C T Sulaiman; Indira Balachandran; K P Subhash Chandran (Vegetos, 2022)

Propolis: chemical diversity and challenges in quality control - Deepak Kasote; Vassya Bankova; Alvaro M. Viljoen (Phytochemistry Reviews, 2022)

Gut–Brain Axis, Neurodegeneration and Mental Health: A Personalized Medicine Perspective - Alisha Chunduri; S. Deepak Mohan Reddy; M. Jahanavi; C. Nagendranatha Reddy (Indian Journal of Microbiology, 2022)

Novel Nanostructured Lipid Carriers Co-Loaded with Mesalamine and Curcumin: Formulation, Optimization and In Vitro Evaluation - Ankit Awasthi; Bimlesh Kumar; Monica Gulati; Sukriti Vishwas; Leander Corrie; Jaskiran Kaur; Rubiya Khursheed; Rozhan Arif Muhammed; Duran Kala; Omji Porwal; Malakapogu Ravindra Babu; M. V. N. L. Chaitanya; et al. (Pharmaceutical Research, 2022)

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.

Sun-Dried Sugarcane Press Mud Could be a Prospective Feedstuff for Swine Production - Subhasish Sahu; B. H. M. Patel; Archana Sarangi; Dinesh Kumar; M. S. Mahesh; Deepak Upadhyay; Triveni Dutt (Sugar Tech, 2022)

Coastal vulnerability assessment using Geospatial technologies and a Multi-Criteria Decision Making approach – a case study of Kozhikode District coast, Kerala State, India - K. Ch. V. Naga Kumar; P. M. Deepak; K. K. Basheer Ahammed; Kakani Nageswara Rao; Girish Gopinath; V. P. Dinesan (Journal of Coastal Conservation, 2022)

Deciphering the immunoboosting potential of macro and micronutrients in COVID support therapy - Gaber El-Saber Batiha; Ali I. Al-Gareeb; Safaa Qusti; Eida M. Alshammari; Deepak Kaushik; Ravinder Verma; Hayder M. Al-kuraishy (Environmental Science and Pollution Research, 2022)

Molecular detection of tick-borne pathogens harbored by ticks collected from local breed (Non-descript) of cattle in the chhattishgarh state of India - Suresh Gulabrao Jadhao; Sushanta Pal; Sonali Deepak Borkar; Gajanan M. Chigure; Subrhodal Nath; Prabhir Kumar Sanyal; Sachin Sudhakar Waghmare; Sachin Kumar (International Journal of Tropical Insect Science, 2022)

Transcriptomic analysis of changes in Citrus × microcarpa gene expression post Xanthomonas citri subsp. citri infection - Anuj Sharma; Christopher M. Ference; Deepak Shantharaj; Elizabeth A. Baldwin; John A. Manthey; Jeffrey B. Jones (European Journal of Plant Pathology, 2022)

Ameliorative effect of Dillenia indica fruits against doxorubicin-induced cardiomyocyte toxicity - Kalyani Tene; Kalyan Kumar; Deepak Bharadwaj Pemmaraju; Jagadeesh Kumar; P. A. Shantanu; Ranadeep Gogoi; V. G. M. Naidu (Advances in Traditional Medicine, 2021)

Status of health and conservation classification of tropical coral reefs in Lakshadweep archipelago - M. Gopi; J. Joyson Joe Jeevamani; S. Goutham; Nina Tabitha Simon; V. Deepak Samuel; K. R. Abhilash; R. S. Robin; G. Hariharan; R. Muruganandam; P. Krishnan; R. Purvaja; R. Ramesh (Wetlands Ecology and Management, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Corrigendum: Effect of COVID-19 Anthropause on Water Clarity in the Belize Coastal Lagoon - Ileana A. Callejas; Christine M. Lee; Deepak R. Mishra; Stacey L. Felgate; Claire Evans; Abel Carrias; Andria Rosado; Robert Griffin; Emil A. Cherrington; Mariam Ayad; Megha Rudresh; Benjamin P. Page; et al. (Frontiers in Marine Science, 2021)

Middle East Respiratory Syndrome (MERS) Virus—Pathophysiological Axis and the Current Treatment Strategies - Abdullah M Alnuqaydan; Abdulmajeed G Almutary; Arulmalar Sukamaran; Brian Tay Wei Yang; Xiao Ting Lee; Wei Xuan Lim; Yee Min Ng; Rania Ibrahim; Thiviya Darmarajan; Satheeshkumar Nanjappan; Jestin Chellian; Mayuren Candasamy; et al. (AAPS PharmSciTech, 2021)

Impact of heat and drought stress on phenological development and yield in bread wheat - K. J. Yashavanthakumar; Vijendra S. Baviskar; Sudhir Navathe; Ravindra M. Patil; Juned H. Bagwan; Deepak N. Bankar; Vitthal D. Gite; K. Gopalareddy; Chandra Nath Mishra; H. M. Mamrutha; Sanjay Kumar Singh; Shreenivas A. Desai; et al. (Plant Physiology Reports, 2021)

Genome Analysis of Bacillus aryabhattai to Identify Biosynthetic Gene Clusters and In Silico Methods to Elucidate its Antimicrobial Nature - Deepak A. Yaraguppi; Sanjay H. Deshpande; Zabin K. Bagewadi; Sudeep Kumar; Uday M. Muddapur (International Journal of Peptide Research and Therapeutics, 2021)

Impact of long term uplift on stream networks in tectonically active Northern Hill Range, Kachchh palaeo-rift basin, western India - Akash Padmalal; Deepak M Maurya; Naimisha P Vanik; Mohamedharoon A Shaikh; Prabhuti Tiwari; Laxman S Chamyal (Journal of Mountain Science, 2021)

Effect of COVID-19 Anthropause on Water Clarity in the Belize Coastal Lagoon - Ileana A. Callejas; Christine M. Lee; Deepak R. Mishra; Stacey L. Felgate; Claire Evans; Abel Carrias; Andria Rosado; Robert Griffin; Emil A. Cherrington; Mariam Ayad; Megha Rudresh; Benjamin P. Page; et al. (Frontiers in Marine Science, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic halted human activities globally in multiple sectors including tourism. As a result, nations with heavy tourism, such as Belize, experienced improvements in water quality. Remote sensing technologies can detect impacts of “anthropauses” on coastal water quality. In this study, moderate resolution imaging spectroradiometer (MODIS) satellite data were employed along the Belizean coast to investigate impacts of the COVID-19 shutdown on water quality. The attenuation coefficient at 490 nm, K d (490), was used as an indicator of water quality, with a lower K d (490) indicating increased water clarity. Four Coastal Management Zones were characterized by marine traffic as high traffic areas (HTAs) and two as low traffic areas (LTAs). Monthly composites for two periods, 2002–2019 (baseline) and 2020 were examined for K d (490). For months prior to the COVID-19 shutdown in Belize, there was generally no significant difference in K d (490) ( p > 0.05) between 2020 and baseline period in HTAs and LTAs. Through the shutdown, K d was lower in 2020 at HTAs, but not for LTAs. At the LTAs, the K d (490)s observed in 2020 were similar to previous years through October. In November, an unusually active hurricane season in 2020 was associated with decreased water clarity along the entire coast of Belize. This study provides proof of concept that satellite-based monitoring of water quality can complement in situ data and provide evidence of significant water quality improvements due to the COVID-19 shutdown, likely due to reduced marine traffic. However, these improvements were no longer observed following an active hurricane season.

N-Benzylation of 6-aminoflavone by reductive amination and efficient access to some novel anticancer agents via topoisomerase II inhibition - Nitin M. Thorat; Aniket P. Sarkate; Deepak K. Lokwani; Shailee V. Tiwari; Rajaram Azad; Shankar R. Thopate (Molecular Diversity, 2021)

Molecular profiling of blast resistance genes and evaluation of leaf and neck blast disease reaction in rice - Haniyambadi B. Manojkumar; Chikkaballi A. Deepak; Kodihally M. Harinikumar; M. P. Rajanna; Belthur Chethana (Journal of Genetics, 2020)

In an exploratory randomized, double-blind, placebo-controlled, cross-over study, psychoactive doses of intravenous delta-9-tetrahydrocannabinol fail to produce antinociceptive effects in healthy human volunteers - Emmanuelle A. D. Schindler; Ashley M. Schnakenberg Martin; R. Andrew Sewell; Mohini Ranganathan; Anna DeForest; Brian P. Pittman; Albert Perrino; Deepak C. D’Souza (Psychopharmacology, 2020)

Emerging era of “somes”: polymersomes as versatile drug delivery carrier for cancer diagnostics and therapy - Abhishek Kumar Sharma; Parteek Prasher; Alaa A. Aljabali; Vijay Mishra; Himanshu Gandhi; Sunil Kumar; Srinivas Mutalik; Dinesh Kumar Chellappan; Murtaza M. Tambuwala; Kamal Dua; Deepak N. Kapoor (Drug Delivery and Translational Research, 2020)

Chemical composition, antioxidant and antiproliferative activities of essential oil from rhizome and leaves of Curcuma mutabilis Škorničk., M. Sabu & Prasanthk., endemic to Western Ghats of India - T. Soumya; P. R. Jayasree; M. Deepak; P. R. Manish Kumar (Natural Product Research, 2020)

Metabolomics-based biomarkers of Fusarium wilt disease in watermelon plants - Deepak M. Kasote; Guddadarangavvanahally K. Jayaprakasha; Jashbir Singh; Kevin Ong; Kevin M. Crosby; Bhimanagouda S. Patil (Journal of Plant Diseases and Protection, 2020)

Assessment of yield gaps on global grazed‐only permanent pasture using climate binning - Leonardo A. Monteiro; Andrew M. Allee; Eleanor E. Campbell; Lee R. Lynd; Johnny R. Soares; Deepak Jaiswal; Julianne de Castro Oliveira; Murilo dos Santos Vianna; Ashley E. Morishige; Gleyce K. D. A. Figueiredo; Rubens A. C. Lamparelli; Nathaniel D. Mueller; et al. (Global Change Biology, 2020)
To meet rising demands for agricultural products, existing agricultural lands must either produce more or expand in area. Yield gaps (YGs)—the difference between current and potential yield of agricultural systems—indicate the ability to increase output while holding land area constant. Here, we assess YGs in global grazed‐only permanent pasture lands using a climate binning approach. We create a snapshot of circa 2000 empirical yields for meat and milk production from cattle, sheep, and goats by sorting pastures into climate bins defined by total annual precipitation and growing degree‐days. We then estimate YGs from intra‐bin yield comparisons. We evaluate YG patterns across three FAO definitions of grazed livestock agroecosystems (arid, humid, and temperate), and groups of animal production systems that vary in animal types and animal products. For all subcategories of grazed‐only permanent pasture assessed, we find potential to increase productivity several‐fold over current levels. However, because productivity of grazed pasture systems is generally low, even large relative increases in yield translated to small absolute gains in global protein production. In our dataset, milk‐focused production systems were found to be seven times as productive as meat‐focused production systems regardless of animal type, while cattle were four times as productive as sheep and goats regardless of animal output type. Sustainable intensification of pasture is most promising for local development, where large relative increases in production can substantially increase incomes or “spare” large amounts of land for other uses. Our results motivate the need for further studies to target agroecological and economic limitations on productivity to improve YG estimates and identify sustainable pathways toward intensification.

RNA-seq reveals outcome-specific gene expression of MMP7 and PCK1 in biliary atresia - Priya Ramachandran; Deepak Balamurali; J. John Peter; M. Milner Kumar; Mohamed Safwan; Mukul Vij; Mohamed Rela; Sundarasamy Mahalingam (Molecular Biology Reports, 2019)

Uplift induced structurally controlled landscape development: example from fault bounded Jumara and Jara domes in Northern Hill Range, Kachchh, Western India - Mohamedharoon A. Shaikh; Deepak M. Maurya; Naimisha P. Vanik; Akash Padmalal; Laxman S. Chamyal (Geosciences Journal, 2019)

Santalum molecular biology: molecular markers for genetic diversity, phylogenetics and taxonomy, and genetic transformation - Jaime A. Teixeira da Silva; Mafatlal M. Kher; Deepak Soner; M. Nataraj; Judit Dobránszki; Melissa A. Millar (Agroforestry Systems, 2018)

Cytological and immunocytological detection and differentiation of Marek’s disease and lymphoid leucosis in poultry - M. Asok Kumar; M. Palanivelu; R. Barathidasan; Deepak Kumar; S. D. Singh; Shyma K. Lateef; Rajendra Singh; K. Dhama (VirusDisease, 2018)

Multivariate statistical analysis approach for prediction of blast-induced ground vibration - Vivek K. Himanshu; M. P. Roy; A. K. Mishra; Ranjit Kumar Paswan; Deepak Panda; P. K. Singh (Arabian Journal of Geosciences, 2018)

The effects of cannabidiol (CBD) on cognition and symptoms in outpatients with chronic schizophrenia a randomized placebo controlled trial - Douglas L. Boggs; Toral Surti; Aarti Gupta; Swapnil Gupta; Mark Niciu; Brian Pittman; Ashley M. Schnakenberg Martin; Halle Thurnauer; Andrew Davies; Deepak C. D’Souza; Mohini Ranganathan (Psychopharmacology, 2018)

Pathological and molecular studies of the renal trematode Paratanaisia bragai in Indian peafowls (Pavo cristatus) - M. Asok Kumar; Deepak Kumar; Munuswamy Palanivelu; Latchumikanthan Annamalai; Karikalan Mathesh; Rajendra Singh; Anil Kumar Sharma; Kuldeep Dhama (Acta Parasitologica, 2018)
Endoparasitic diseases are commonly encountered in free-ranging birds. Although not all endoparasites cause disease, persistent infection with large numbers of parasites almost always affects normal physiological functions, leading to deleterious effects on the host. This paper describes the anatomopathological alterations caused by the renal trematode Paratanaisia bragai in Indian peafowl (n = 3) and examines the phylogeny of these and related parasites. Peafowl from forests in and around the Bareilly region, Uttar Pradesh, India, were necropsied, and microscopic and molecular investigations were performed. The peafowl were confirmed to be infected with P . bragai . Significant gross pathological lesions suggested nephrosis, and microscopic findings indicated a mild-to-moderate degree of nephrosis caused by the parasites in the tissue. The parasites were identified as P . bragai by histomorphological analysis of adult and eggs in the ureters, and the identification was confirmed by PCR and phylogenetic analysis. Nucleotide sequencing of the PCR products from the renal trematodes recovered from Indian peafowl revealed a close association with P . bragai from Columbiformes in the United Kingdom and Spain. The pathology and molecular epidemiology of parasitic diseases affecting peafowl is not well understood in India. This is the first report from India and the second report worldwide to document P . bragai infection in peafowl.

Innovative graphene microbial platforms for domestic wastewater treatment - Hanaa M. Hegab; Ahmed ElMekawy; Ben van den Akker; Milena Ginic-Markovic; Christopher Saint; Gayle Newcombe; Deepak Pant (Reviews in Environmental Science and Bio/Technology, 2018)

Influence of secondary compression on undrained strength of soft kaolinites - Sudhakar M. Rao; G. B. Deepak (Marine Georesources & Geotechnology, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Process effluents and mine tailings: sources, effects and management and role of nanotechnology - Dipti Prakash Mohapatra; Deepak M. Kirpalani (Nanotechnology for Environmental Engineering, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Simulating the impact of land use/land cover change and climate variability on watershed hydrology in the Upper Brantas basin, Indonesia - Ari Setyorini; Deepak Khare; Santosh M. Pingale (Applied Geomatics, 2017)

Perturbations and 3R in carbon management - Deepak Pant; Virbala Sharma; Pooja Singh; Manoj Kumar; Anand Giri; M P Singh (Environmental Science and Pollution Research, 2017)

The impact of assimilating MeghaTropiques SAPHIR radiances in the simulation of tropical cyclones over the Bay of Bengal using the WRF model - M. Dhanya; Deepak Gopalakrishnan; A. Chandrasekar; Sanjeev Kumar Singh; V.S. Prasad (International Journal of Remote Sensing, 2016)

Sandalwood: basic biology, tissue culture, and genetic transformation - Jaime A. Teixeira da Silva; Mafatlal M. Kher; Deepak Soner; Tony Page; Xinhua Zhang; M. Nataraj; Guohua Ma (Planta, 2016)

Molecular identification and systematic assessment of Labidocera madurae A. Scott, 1909 (calanoid copepod) from Lakshadweep Archipelago, southwest coast of India, based on mitochondrial COI gene sequences - V. F. Sanu; S. Bijoy Nandan; J. Deepak; M. Harikrishnan (Marine Biodiversity, 2016)

A comparative study with biologically and chemically synthesized nZVI: applications in Cr (VI) removal and ecotoxicity assessment using indigenous microorganisms from chromium-contaminated site - K. V. G. Ravikumar; Deepak Kumar; A. Rajeshwari; G. M. Madhu; P. Mrudula; Natarajan Chandrasekaran; Amitava Mukherjee (Environmental Science and Pollution Research, 2016)

Identification of putative SNPs in progressive retinal atrophy affected Canis lupus familiaris using exome sequencing - Bhaskar Reddy; Divyesh N. Kelawala; Tejas Shah; Anand B. Patel; Deepak B. Patil; Pinesh V. Parikh; Namrata Patel; Nidhi Parmar; Amit B. Mohapatra; Krishna M. Singh; Ramesh Menon; Dipal Pandya; et al. (Mammalian Genome, 2015)

Molecular Detection of New Delhi Metallo-Beta-Lactamase-1 (NDM-1) Positive Bacteria from Environmental and Drinking Water Samples by Loop Mediated Isothermal Amplification of bla NDM-1 - P. Rathinasabapathi; Deepak S. Hiremath; Rex Arunraj; M. Parani (Indian Journal of Microbiology, 2015)

Design, synthesis of quinolinyl Schiff bases and azetidinones as enoyl ACP-reductase inhibitors - Shrinivas D. Joshi; Uttam A. More; Deepak Parkale; Tejraj M. Aminabhavi; Andanappa K. Gadad; Mallikarjuna N. Nadagouda; Rahul Jawarkar (Medicinal Chemistry Research, 2015)

Tidal Influence on the Diel Vertical Migration Pattern of Zooplankton in a Tropical Monsoonal Estuary - G. Vineetha; R. Jyothibabu; N. V. Madhu; K. K. Kusum; P. M. Sooria; A. Shivaprasad; P. D. Reny; M. P. Deepak (Wetlands, 2015)

Genetic Predisposition to Diabetic Nephropathy: Evidence for a Role of ACE (I/D) Gene Polymorphism in Type 2 Diabetic Population from Kutch Region - Deepak N. Parchwani; Kamlesh M. Palandurkar; D. Hema Chandan Kumar; Darshan J. Patel (Indian Journal of Clinical Biochemistry, 2015)

Cross-species transferability of microsatellite markers from Fusarium oxysporum for the assessment of genetic diversity in Fusarium udum - Sudheer Kumar; Shalini Rai; Deepak Kumar Maurya; Prem Lal Kashyap; Alok K. Srivastava; M. Anandaraj (Phytoparasitica, 2013)

Internal sedimentary architecture and coastal dynamics as revealed by ground penetrating radar, Kachchh coast, western India - Shashi B. Shukla; Vikas M. Chowksey; Siddharth P. Prizomwala; Vishal M. Ukey; Nilesh P. Bhatt; Deepak M. Maurya (Acta Geophysica, 2013)

Study of atmospheric stagnation, recirculation and ventilation potential at Narora Atomic Power Station NPP site - Deepak Kumar; Avinash Kumar; Vimal Kumar; Jaivender Kumar; P. M Ravi (Environmental Monitoring and Assessment, 2013)

Intestinal iron absorption during suckling in mammals - David M. Frazer; Deepak Darshan; Gregory J. Anderson (BioMetals, 2011)

The Impact of Future Land Use Scenarios on Runoff Volumes in the Muskegon River Watershed - Deepak K. Ray; Jonah M. Duckles; Bryan C. Pijanowski (Environmental Management, 2010)

Synthesis of Novel Spiro-Oxazino-Quinoline Derivatives and Study of Their Photophysical Properties - Bhupendra S. Rane; Muddassar A. Kazi; Sandeep M. Bagul; Deepak P. Shelar; Raghunath B. Toche; Madhukar N. Jachak (Journal of Fluorescence, 2010)

A metabolic and functional overview of brain aging linked to neurological disorders - Najma Z. Baquer; Asia Taha; Pardeep Kumar; P. McLean; S. M. Cowsik; R. K. Kale; R. Singh; Deepak Sharma (Biogerontology, 2009)

Keratins: Markers of cell differentiation or regulators of cell differentiation? - Milind M. Vaidya; Deepak Kanojia (Journal of Biosciences, 2007)

Regulation of systemic iron homeostasis: how the body responds to changes in iron demand - Gregory J. Anderson; Deepak Darshan; Sarah J. Wilkins; David M. Frazer (BioMetals, 2007)

Negative effect of chromosome 1A on dough strength shown by modification of 1D addition in durum wheat (Triticum durum) - Monika Garg; Harcharan Singh Dhaliwal; Parveen Chhuneja; Deepak Kumar; Quan-Wen Dou; Hiroyuki Tanaka; Hala M. M. Elamein; Hisashi Tsujimoto (Theoretical and Applied Genetics, 2007)

Pathognomonic genetic expression profile within peripheral blood mononuclear cells of rheumatic heart disease patients - M. Iqbal Baba; Deepak Kaul; Anil Grover (Molecular and Cellular Biochemistry, 2006)

Assessment of biochemical components and enzyme activities in the estuarine crab Scylla tranquebarica from naphthalene contaminated habitants - K. Vijayavel; C. Anbuselvam; M. P. Balasubramanian; V. Deepak Samuel; S. Gopalakrishnan (Ecotoxicology, 2006)

Tryptophan residue is essential for immunoreactivity of a diagnostically relevant peptide epitope of A. fumigatus - Neel Kamal; Shantanu Chowdhury; Taruna Madan; Deepak Sharma; M. Attreyi; Wahajul Haq; Seturam Bandacharya Katti; Anil Kumar; P. Usha Sarma (Molecular and Cellular Biochemistry, 2005)

Chronology of Late Pleistocene environmental changes in the lower Mahi basin, western India - Navin Juyal; Rachna Raj; Deepak M. Maurya; Laxman S. Chamyal; Ashok K. Singhvi (Journal of Quaternary Science, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)